Comparison between Titanium Elastic Nailing (TEN) and Dynamic Compression Plating (DCP) in Femoral Diaphyseal Fractures in Children - Khan, Md Abdul Gaffar; Hannan, M A; Mistry, Goutam Baran; Mallik, Sumon; Majumder, Lata; Ahmed, Mumit (Jalalabad Medical Journal, 2026)
Femoral shaft fractures are among the most common fractures of the lower extremity in children. Various methods of treatment can be used successfully, depending on the age of the child and the type of fracture. Immediate application of a spica cast, or traction followed by a cast, remains the standard management for most of these fractures in children. Operative treatment modalities include intramedullary nailing by flexible or rigid nails, external fixation, traditional open reduction and plate fixation, and submuscular bridging plating. The objective of this study was to compare the outcome of titanium elastic nailing and dynamic compression plating in diaphyseal fractures of the femur of children aged 6-12 years. This cross-sectional comparative study was conducted in the department of Orthopaedics, Sylhet MAG Osmani Medical College Hospital, during the period from 1st January 2016 to 31st December 2017. Thirty-six children with femoral diaphyseal fractures aged between 6-12 years of both sexes were included. Patients with pathological fractures, open fractures, fractures with associated neurovascular injury, those who weighed more than 49 kg, those with fractures longer than 2 weeks old and those unwilling to take part in the study were excluded. They were divided by random allocation into group-A (odd number) and group-B (even number) each comprised of 18 patients and treated with titanium elastic nailing and dynamic compression plating, respectively. Outcome was assessed with Flynn criteria at 6 months follow-up. The mean age was [9.56±1.98 years versus 9.67±1.46 years; p>0.05] and sex [15 (83.3%) male and 3 (16.7%) female versus 16 (88.9%) male and 2 (11.15%) female; p>0.05] did not differ significantly between group-A and group-B. Operation time [60.83±11.79 minutes versus 72.06±10.99 minutes; p<0.01], length of postoperative hospital stay [12.00±1.94 days versus 15.72±3.10 days; p<0.01] and time of union [11.11±1.71 weeks versus 12.00±0.0 weeks; p<0.05] were significantly shorter in group A than in group-B. Postoperative mobilization [2.61±1.72 days versus 2.50±0.71 days; p>0.05); time of weight bearing [6.22±0.65) weeks versus 6.33±0.77 weeks; p>0.05] did not differ significantly between the two treatment groups. The recorded complications of entry point bursitis, chronic discharge, mild pain, malalignment did not differ significantly between the two groups. Excellent functional outcome was more in group-A compared to group-B (83.3% versus 66.7%) but not statistically significant (p>0.05). This study concludes that there is no significant difference between functional outcome in TENS group and DCP group, though TENS group has slightly better outcome. Jalalabad Med J 2025; 22 (2): 61-66